DETAILED ANALYSIS OF VASCULAR STIFFNESS IN PATIENTS WITH CHRONIC HEART FAILURE - Pietschner, Robert; Kolwelter, Julie; Bosch, Agnes; Striepe, Kristina; Kannenkeril, Dennis; Ott, Christan; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (Journal of Hypertension, 2022)
OBJECTIVE: Risk factors for chronic heart failure (CHF) lead as well to vascular stiffness of the large arteries, increasing thereby the afterload imposed on the left ventricle and deteriorating the clinical condition of CHF. The aim of this project was twofold: to compare vascular stiffness of patients with CHF (CHF+) to those without CHF (CHF-) and to analyse whether vascular stiffness is related to the severity of CHF. DESIGN AND METHOD: In this cross-sectional project a total of 223 patients were included (CHF+: n = 105, CHF-: n = 118). Patients in an euvolaemic state with a reduced left ventricular ejection fraction (LVEF) were included in the CHF+ group. The measurement of the pulse wave velocity (PWV), the most accepted vascular stiffness parameter, and the recording of the arterial pulse wave were performed using the SphygmoCor TM XCEL System under resting conditions. Under ambulatory conditions, blood pressure (BP) and vascular stiffness parameters were assessed by a validated device (Mobil-O-Graph, I.E.M.) over 24 hours. Additionally, blood and spot urine samples were used to measure laboratory markers, in particular NT-pro-BNP. RESULTS: Vascular stiffness parameters between the CHF+ and the CHF- group differed for resting central SBP (CHF+: 116.66 ± 15.18 mmHg, CHF-: 122.83 ± 15.87 mmHg, p = 0.004) and central augmentation index (CHF+: 21.24 ± 11.76 %, CHF-: 13.69 ± 11.49 %, p = <0.001) as well as for ambulatory central SBP (CHF+: 114.46 ± 15.35 mmHg, CHF-: 120.69 ± 13.97 mmHg, p = 0.007) and PWV (CHF+: 9.39 ± 1.56 m/s, CHF-: 8.19 ± 1.65 m/s, p = <0.001). In patients with CHF, greater levels of NT-pro-BNP were related to a higher central SBP (r = 0.292, p = 0.005), higher PWV (r = 0.340, p = <0.001) and a trend to higher central PP (r = 0.198, p = 0.058), after full adjustment for CHF risk factors and gender. In accordance, higher levels of NT-pro-BNP were related to a higher ambulatory peripheral PP (r = 0.322, p = 0.002) and total peripheral resistance (r = 0.227, p = 0.041). CONCLUSIONS: In patients with stable CHF we observed a worse vascular stiffness and function, compared to patients with no CHF. The extent of vascular stiffness and dysfunction was related to the severity of CHF.
CRIS-Team Scopus Importer:2022-09-09